MAPPING OF CHLOROPHYLL-A DISTRIBUTION USING LANDSAT 8 IMAGERY IN DUMAI WATERS WEST OF DUMAI CITY RIAU PROVINCE - Debby Irfandinata; Musrifin Galib; Elizal Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT            Chlorophyll-a was the green pigment found in phytoplankton. Chlorophyll-a can be used as an fertility indicator and primary productivity of the sea. Chlorophyll absorbs red and blue colors, and reflects green color. This research was conducted on 5-9 May 2018 with the research area of East Westwaters of Dumai in Riau Province, this research goal is to determine: the distribution of chlorophyll-a in the waters of West Dumai. The survey method was applied in this research where the West waters of Dumai is the research area, sampling location were set up purposively which divided into 5 stations. Each station has one sampling point with three repetitions. The results of this research found that the distribution of chlorophyll-a in West Dumai  was not evenly distributed. The highest chlorophyll-a concentration was in the 2018 around settlements because of the nutrient runoff from land. The lowest concentration is found in 2016 because of the dry season that exist throughout 2016.Key words: Chlorophyll-a, West Waters of Dumai, Phytoplankton.